2014
DOI: 10.1590/1809-4503201400040005
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reproducibility of a food frequency questionnaire for adults of São Paulo, Brazil

Abstract: The food frequency questionnaire analyzed has good validity and reproducibility for estimating the food consumption of adults in São Paulo compared to the reference method, so it is an appropriate instrument to be used in epidemiological studies on similar populations. Estimates of polyunsaturated fat and folate should be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 16 publications
3
27
0
4
Order By: Relevance
“…The present study showed agreement between the methods used to estimate dietary intake for the nutritional variables, energy, and six nutrients, representing a larger number of variables than that reported in most studies available, which usually consider only the macronutrients 30 . Based on the data analysis, it can be said that the use of digital technology improves the quality of the data collected when compared to the use of conventional methods, as shown in similar studies 22,23,28,29 .…”
Section: Discussionsupporting
confidence: 72%
“…The present study showed agreement between the methods used to estimate dietary intake for the nutritional variables, energy, and six nutrients, representing a larger number of variables than that reported in most studies available, which usually consider only the macronutrients 30 . Based on the data analysis, it can be said that the use of digital technology improves the quality of the data collected when compared to the use of conventional methods, as shown in similar studies 22,23,28,29 .…”
Section: Discussionsupporting
confidence: 72%
“…Sabe-se que o QFA é um instrumento de boa validade e reprodutibilidade, entretanto não está isento de erros. A coleta de dados realizada por entrevistadores capacitados e treinados minimizou vícios de classificação, contudo é preciso considerar limitações do método, uma vez que depende da memória e da capacidade do entrevistado de relatar os alimentos e porções consumidos (SELEM et al, 2014). Além disso, sabe-se que a obesidade é uma …”
Section: Resultsunclassified
“…As Sabaté points out, there are different methods used for the evaluation of food consumption, the 24-hour Reminder being a useful tool for this purpose, the dietary journal allows to detail the quantities of food and beverages consumed [28][29][30]. The dietary history allows us to evaluate the average food and liquid intake as well as the frequency of consumption questionnaire , the latter being the most widely used, being validated in several languages such as Spanish , Chinese , Guam , for multiethnic populations , in Korean , Danish , Japanese , New Zealand , Brazil , Norway , Australia , among others [31,32,25,[33][34][35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%